2006
DOI: 10.2131/jts.31.529
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Home Cage Locomotion in Cynomolgus Monkeys

Abstract: -The profiles of home cage locomotor activity and its rhythmicity were investigated using a camera system for 4 consecutive days in cynomolgus monkeys. Nine male and nine female cynomolgus monkeys were used in this study, and were found to have the same profile in nocturnal behavior in that they were mostly inactive during the night. The locomotor activity of both sexes showed a normal activity and inactivity rhythm, which had an inverse relationship between normal activity and inactivity, showing a fluctuatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Though few studies have comprehensively studied the subject, reports in the literature have demonstrated that ICP values in adult cynomolgus macaques fall into a similar range of normal pressures. A combination of our observations, the activity traces seen in Fig 3B, Fig3C, and Fig 4A, and documented reports of postural preferences in awake and asleep macaques suggest the possibility of diurnal variation of ICP in cynomolgus macaques due to associated variation in posture and movement (44, 45). Deviation from a circadian pattern can provide an additional piece of evidence for the onset of a pathological process in a monitored macaque.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Though few studies have comprehensively studied the subject, reports in the literature have demonstrated that ICP values in adult cynomolgus macaques fall into a similar range of normal pressures. A combination of our observations, the activity traces seen in Fig 3B, Fig3C, and Fig 4A, and documented reports of postural preferences in awake and asleep macaques suggest the possibility of diurnal variation of ICP in cynomolgus macaques due to associated variation in posture and movement (44, 45). Deviation from a circadian pattern can provide an additional piece of evidence for the onset of a pathological process in a monitored macaque.…”
Section: Resultssupporting
confidence: 85%
“…Comparisons of daytime and nighttime values of the data obtained through frequency spectrum analysis indicated that measured pressures tended to display increased values at night (p<0.01). This finding, a group measure, can reflect the general preference for a seated, head-down posture during the night (45). Alongside the understanding that supine or seated postures can produce increased ICP relative to standing, upright postures, the output of increased nighttime intracranial pressure in this set of macaques represented a fairly reasonable outcome (46).…”
Section: Resultsmentioning
confidence: 99%
“…Though few studies have comprehensively studied the subject, reports in the literature have demonstrated that ICP values in adult cynomolgus macaques fall into a similar range of normal pressures. A combination of our observations, the activity traces seen in Figs 3B, 3C and 4A, and documented reports of postural preferences in awake and asleep macaques suggest the possibility of diurnal variation of ICP in cynomolgus macaques due to associated variation in posture and movement [52,53]. Deviation from a circadian pattern can provide an additional piece of evidence for the onset of a pathological process in a monitored macaque.…”
Section: Intracranial Pressuresupporting
confidence: 81%
“…Comparisons of daytime and nighttime values of the data obtained through frequency spectrum analysis indicated that measured pressures tended to display increased values at night (p<0.01). This finding, a group measure, can reflect the general preference for a seated, head-down posture during the night [53]. Alongside the understanding that supine or seated postures can produce increased ICP relative to standing, upright postures, the output of increased nighttime intracranial pressure in this set of macaques represented a fairly reasonable outcome [54].…”
Section: Intracranial Pressurementioning
confidence: 85%
“…Various physiological measures were also recorded during the sessions (heart rate, blood pressure, body temperature), but locomotor activity was chosen as the primary endpoint to more closely mimic those studies conducted by our group in rats. Previous work by others using Cynomolgus monkeys had also demonstrated the successful use of cage movement to establish daily rhythms (Kim and Han 2006). Further analyses of the physiological endpoints may reveal rhythm changes not in step with cage activity.…”
Section: Discussionmentioning
confidence: 97%